Pengaruh Crm (Customer Relationship Management) Terhadap Kepuasan Pembelian di Farmers Market Botani Square - Glori S Napitupulu; Ilham Hasrimi; Mochamad Bintang; Rachel Sofia Audina; Agung Prayudha Hidayat; Astiani Safitri (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Maintaining the best possible relationship with customers is part of Customer Relationship Management (CRM). The goal is to keep customers loyal and make the company make more money. Leading companies have incorporated CRM into their marketing strategies in an effort to increase sales. The Farmers Market company has implemented a customer relationship management (CRM) system; however, there has been no evaluation of their CRM model to identify profitable marketing strategies or customer retention opportunities. To conduct this investigation, a survey had to be conducted on a sample of 55 current Farmers Market consumers. Using the partial least squares method, the analysis will be conducted with the help of the SmartPLS 2.0 program. The findings of the analysis show that, overall, CRM variables relating to the impact of human resources on customer loyalty and customer satisfaction provide satisfactory results. Customer satisfaction is significantly influenced by each HR variable. While all other variables did contribute to the results, they were not statistically significant. This section of the study concludes with an analysis of the impact of Farmers' Market management and suggestions for improvement.